(untitled) (Journal of the College of Basic Education, 2022)
THE RESEARCH IMPORTANCE SPECIFICAT BY THE NEED TO STUDIES TRAINING PROGRAMS CARE S FOR EFFECTIVE TRANING ESPECIALLY IN BASKETBALL GAME. ..THE RESEARCH PROBLEM IS THE BIG LOSES OF IRAQI BASKETBALL TEAMS WITH OUT EXPECTED CLEAR DEVELOPMENT GUIED IT TO ADVANCE COUNTRIES ,ALSO THE WEAKNESS OF THE ACTIVITY PERFORMANCE… THE RESEARCH SAMPLE IS 16 YOUNG PLAYERS DIVIDED TO TWO EXPEREMENTAL GROUPS FIRST GROUP TRAINING WITH PALISTIC STYLE SECOND GROUP TRAINING WITH PLAYOMETRICS STYLE … THE RESEARCHER BUILD UP CIRCLE TRAINING PROGRAM WITH TWO UNITS AWEEK THE RESEARCHER REACH TO MANY CONCLUSIONS MOST IMPORTANT IS THAT THE PALISTICE STYLE BETTER PLAYOMETRICS STYLE IN DEVELOPMENT ALL RESEARCH VARIABLS (TRAINING CARDIAC STATE, CARDIAC ENERGE,AND BASKETBALL ACTIVITY PERFORMANCE) ,THE PLAYOMETRIC STYLE DEVELOPED THE CARDIAC VARIABLS BUT UNSIGNIFICANT DEFERANCES FOR BASKETBALL ACTIVITY PERFORMANCE ,FROME OTHER SIDE MYBE DEFERANT WITH ANOTHER SAMPLES.. THE RESEARHER SUGGEST MANY RECOMMENATIONS SUCH AS DEPENED ON PALISTIC STYLE IN DEVELOPING RESEARCH VARIABLS FOR BASKETBALL YOUNG PLAYERS (17_18) YEARS , ALSO THE TRANING PROGRAME WHICH THE RESEARCHER BUILD IT UP ,ALSO THERE MUST BE ABIG PHYSICAL PREPARATION ESPECIALLY MAX STRENGTH BEFORE TRAINING BY THESE STYLS ,IN ADDITION RESEARCHER SUGGEST ANOTHER RESEARCHS TO ANOTHER SAMPLES.